Perbandingan Pemberian Ekstrak Kayu Siwak (Salvadora Persica) 50% Dan Larutan Sodium Fluorida 2% Terhadap Ketahanan Email Gigi Rattus Norvegicus - Diana, Sherli; Triawan, Andi (Insisiva Dental Journal, 2012)
Miswak (Salvadora Persica) Has A Substance Of Anti Bacterium Which Can Decrease The Amount Of Bacteria In Mouth So That The Tooth Become Health And Prevent Dental Caries And Also The Disinfectant Effect Of Miswak That Can Discontinue Gum Bleeding. While Sodium Fluoride Pursue Decalcification And Enamel Condensation In Mouth And Also Remineralization Of Tooth Enamel. The Aim Of This Research Is To Compare The Effect Between Extract Of Wood Miswak 50% And Solution Of Sodium Fluoride 2% To Enamel Resistant In Rattus Norvegicus On Tooth. The Subjects This Research Are 10 Rattus Norvegicus Which 20 Days Old. During 30 Day Of Rattus Norvegicus Is Given The Same Feed And Drink With Different Intervention That Is Lower Jaw Teeth Of 5 Rattus Norvegicus Was Dabbing With Extract Of Wood Miswak 50% And Other Lower Jaw Teeth Of 5 Rattus Norvegicus Was Dabbing With Solution Of Sodium Fluoride 2%. After 30 Day, All Rattus Norvegicus Were Decapited By Using Ether. Afterwards, Lower Jaw Of Rattus Norvegicus Was Extracted, Next Nub With 37% Phosphoric Acid Gel During 60 Second Then Cleaned With Refine Water And Digitally Periapical Roentgen. Then, They Were Scored To Get Data Of Each Variable And Statistical Test With Mann-Whitney Test. Statistical Test With MannWhitney Test Resulted ( P=0,419) Because ( P>0,05) Means There Is Influence Which Not Significantly Different Between Extract Of Wood Miswak 50% And Solution Of Sodium Fluoride 2%. Research Result Indicates That Extract Of Wood Miswak 50% And Solution Of Sodium Fluoride 2% Have Influence Which Not Significantly Different To Enamel Resistance Of Rattus Norvegicus Tooth Which Assessed With Score Using 5 Point Of Belief Scale.